Birds of Prey of the West : A Field Guide - Wheeler, Brian K., 1955- (Book collections on Project MUSE., 2018)
Birds of Prey of the West and its companion volume, Birds of Prey of the East, are the most comprehensive and authoritative field guides to North American birds of prey ever published. Written and lavishly illustrated with stunning, lifelike paintings by leading field-guide illustrator, photographer, and author Brian Wheeler, the guides depict an enormous range of variations of age, sex, color, and plumage, and feature a significant amount of plumage data that has never been published before. The painted figures illustrate plumage and species comparisons in a classic field-guide layout. Each species is shown in the same posture and from the same viewpoint, which further assists comparisons. Facing-page text includes quick-reference identification points and brief natural history accounts that incorporate the latest information. The range maps are exceptionally accurate and much larger than those in other guides. They plot the most up-to-date distribution information for each species and include the location of cities for more accurate reference. Finally, the guides feature color habitat photographs next to the maps. The result sets a new standard for guides to North America's birds of prey. Lavishly illustrated with stunning, lifelike paintings; Written and illustrated by a leading authority on North American birds of prey; Depicts more plumages than any other guide; Concise facing-page text includes quick-reference identification points; Classic field-guide layout makes comparing species easy; Large, accurate range maps include up-to-date distribution information; Color habitat photographs next to the maps.